Development of an Educational Web Application with an architecture base on the cloud, to facilitate the learning process in programming Logic through pseudocode in Kichwa - Pineda Vega, Jean Pierre (2021)
The purpose of this project is to develop an educational web application that facilitates the learning of programming through the use of pseudocode syntax in Kichwa. Making use of cloud-based services such as cloud functions for servers, CloudBuild for deployment and firebase for hosting and database. This application will link instructions, statements, and operators, which form the basis of programing logic, enabling the generation of a practical and understandable pseudocode that facilitates the teaching of programming. Throughout the development of this model the follow is defined: the structure and syntax of the pseudocode in Kichwa; the creation of data dictionaries, restricted words and terms; definition of data typology, int, string; definition of the control structure syntaxis, statements: if, then, else loop for, while, definition of the architecture of the code analyzer that determines the process of translation of the pseudocode in Kichwa, the creation of the graphic interface. The web application performs an analysis of the pseudocode written by the user; then a translation is carried out through the pseudocode in Kichwa, for its further compilation and execution.